Identitas Budaya dalam Politik Pariwisata: Promosi Strategis Gua Laulawi oleh Otoritas Lokal - Fazlin, Fazlin; Sopacua, Yustina; Nahuaway, Yohana (Universitas Pattimura, 2024)
This article examines the tourism promotion strategies employed by the Tourism Office of Buton Tengah Regency in marketing the Laulawi Cave tourist attraction, with an emphasis on the role of cultural identity as an instrument in local tourism politics. The study aims to analyze the form and effectiveness of marketing communication strategies used by local authorities and to evaluate the outcomes of the strategic plans implemented. This research adopts a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews, direct observation, document analysis, and literature review. The findings reveal that the applied promotional strategies consist of seven main components: advertising, sales promotion, event and experiential marketing, public relations, direct marketing, word-of-mouth marketing, and personal selling. Local cultural identity is positioned as the central attraction across all promotional efforts, highlighting how tourism policy functions as a means of constructing and reinforcing regional imagery. These findings contribute to the broader discourse in social and political sciences, particularly in understanding how local cultural symbols are articulated in tourism destination promotion strategies. The study recommends the importance of integrating cultural narratives with sustainable marketing strategies to support identity-based tourism development.